Hybrid microscopic-mesoscopic traffic simulation - Burghout, Wilco (KTH, Infrastruktur, 2004)
Traffic simulation is an important tool for modelling the operations of dynamic traffic systems and helps analyse the causes and potential solutions of traffic problems such as congestion and traffic safety. Microscopic simulation models provide a detailed representation of the traffic process, which makes them most suitable for evaluation of complicated traffic facilities and Intelligent Transportation Systems that often consist of complex traffic management, safety and information systems. Macroscopic and mesoscopic models on the other hand, capture traffic dynamics in lesser detail, but are faster and easier to apply and calibrate than microscopic models. Therefore they are most suitable for modelling large networks, while microscopic models are usually applied to smaller areas. The objective of this thesis is to combine the strengths of both modelling approaches and diminish their individual weaknesses by constructing a hybrid mesoscopic-microscopic model that applies microscopic simulation to areas of specific interest, while simulating a surrounding network in lesser detail with a mesoscopic model. Earlier attempts at hybrid modelling have concentrated on integrating macroscopic and microscopic models and have proved difficult due to the large difference between the continuous-flow representation of traffic in macroscopic models and the detailed vehicle-and driver-behaviour represented in microscopic models. These problems are solved in this thesis by developing a mesoscopic vehicle-based and event-based model that avoids the (dis)aggregation problems of traffic flows at the inter-model boundaries. In addition, this thesis focuses on the general problems of consistency across the entire hybrid model. The requirements are identified that are important for a hybrid model to be consistent across the models at different levels of detail. These requirements vary from network and route-choice consistency to consistency of traffic dynamics across the boundaries of the micro- and mesoscopic submodels. An integration framework is proposed that satisfies these requirements. This integration framework has been implemented in a prototype hybrid model, MiMe, which is used to demonstrate the correctness of the solutions to the various integration issues. The hybrid model integrates MITSIMLab, a microscopic traffic simulation model, and Mezzo, the newly developed mesoscopic model. Both the hybrid model and the new Mezzo model are applied in a number of case studies, including a network in the North of Stockholm, which show their validity and applicability. The results are promising and support both the proposed integration architecture and the importance of integrating microscopic and mesoscopic models. === QC 20100520